PENGARUH TEKNIK PENILAIAN DAN MANAJEMEN DIRI TERHADAP HASIL BELAJAR FILSAFAT PENDIDIKAN ISLAM - ARIS TRY ANDREAS PUTRA (Jurnal Evaluasi Pendidikan, 2013)
The objectives of this study is to find out the influence of assessment technique and self management toward the students’ philosophy of Islamic education achievement at STAIN Kendari. The design was 2 x 2 treatment by level. The experimental subject consisted of 40 students who were in the fourth semester. The data analysis was used two way anova. The result of study showed that: (1) the students’ philosophy of Islamic education achievement who assessed by performance assessment was higher than the student who assessed by essay assessment, (2) there was an interaction effect between assessment technique and self management toward students’ philosophy of Islamic education achievement, and (3) at the active self management, the students’ philosophy of Islamic education achievement was higher when assessed by performance assessment technique than essay assessment. Based on the result of this study, the researcher suggests in order to consider to the students’ self management in applying the technique of assessment, due to there is no assessment technique fit to all subject.